Integrasi Model Kano ke Dalam Quality Function Deployment: Aplikasi pada Perpustakaan - Thabrani, Gesit (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2016)
Library is one of the important things in university because it can determine the quality of students as a resource that are needed to deal with globalisation. University libraries must offer better quality services in order to satisfy the students as their customers. The purpose of this study is to analyse the customer requirements related to library services by using the planning matrix of quality function deployment (QFD) and integrating Kano Model into it to get better importance requirements. This study is applied to library of Economic Faculty of Universitas Negeri Padang using questionaires survey to 105 respondents who are users or customers of library. This paper reveals that the most important attribute or customer requirement is existence of sufï¬cient number of copies of each speciï¬c study; it also found that 29 attributes can be categorized into 5 must-be attributes, 20 one-dimensional attributes and 4 of them is attractive attributes. The highest quality level of attribute in the library services is Â library cleanliness and tidiness, and attribute that must be priority to improve is availability copier.